The efficacy of the enforcement mechanisms provided for in terms of the consumer protection act 68 of 2008 - Laing, Hadassah Christine (Department of Commercial Law, 2022)
The Consumer Protection Act 68 of 2008 (“the CPA”) has created several enforcement mechanisms through which consumers may vindicate their rights. These enforcement mechanisms have been created to foster efficient redress by promoting forms of alternative dispute resolution which are often more cost-effective, accessible, and speedy. Since the CPA protects human rights and has been enacted to confront South Africa's egregious injustices of the past, ensuring prompt and effective redress is of vital importance. Despite this, South African consumers have experienced difficulties in accessing justice due to some of the CPA's inefficiencies. This dissertation seeks to pinpoint some of the Act's main shortcomings and thereafter proposes solutions. This is done in conjunction with examining the consumer mechanisms and laws put in place in both Nigeria and India as a comparison of how other developing countries have tackled similar issues. A striking takeaway point from both of these case studies is that regulatory bodies often do not have the capacity to play a central role in enforcing the consumer law of these countries. Therefore, it is important that individual consumers are able to vindicate their rights effectively. This dissertation focuses on s 69 of the CPA as somewhat of a stumbling block for consumers to individually enforce their rights. This is because s 69 precludes access to a small claims court in the first instance, presents an unclear hierarchy of redress mechanisms, and rigidly prevents access to a court unless all of the other redress mechanisms have been exhausted. Moreover, this dissertation also critiques the Act's position regarding the court's sole jurisdiction regarding unfair contract terms and the cumbersome two-step procedure prescribed when the quantification of damages is in issue.